Analisis Kesulitan Membaca Permulaan pada Peserta Didik Kelas II Sekolah Dasar Negeri 30 Pontianak Selatan - Melin Tarigas; Kartono Kartono; Suparjan Suparjan; Hery Kresnadi; Asmayani Salimi (PALAPA, 2022)
This study aims to describe the types of early reading difficulties, the causes of early reading difficulties, and explain how teachers overcome early reading difficulties in second grade students. This research use desciptive qualitative approach. The data analysis technique used is the Creswell model which includes four stages, namely preparing data, coding, using code to build descriptions and themes, and showing how these descriptions and themes will be written in a qualitative narrative or report. The results of this study indicate that the types of early reading difficulties in students are not able to recognize and pronounce the letters of the alphabet, difficulty distinguishing the same letters, difficulty reading one consonant letter and one vowel letter, difficulty reading open syllables, difficulty reading syllables into words, and reading is still stuttering. The causes of early reading difficulties are interest factors, motivational factors, parental factors, and teacher factors. The teacher's way of overcoming the difficulty of early reading is by training and familiarizing students to read in their spare time or at school hours in approximately 10 minutes.